Sensitivity Analysis of the Orthorhombic Design Parameters in the Artificially Biaxially Dielectric Crystal - Brand, Jason; Saville, Michael A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A full-wave modeling and simulation analysis method is presented for performing sensitivity analysis of artificial uniaxial and biaxial crystals previously reported for study with waveguide measurement systems. Small occlusions were machined into bulk dielectric material to impose effectively biaxial material properties. Here, the primary design parameters for orthorhombic occlusions are presented. Using multivariate parameter estimation, the effective material properties are characterized in a way that is equivalent to waveguide measurement methods. The advantage in using full-wave simulation allows investigation beyond measurement and fabrication capabilities, but is still limited because of the mesh size needed to model the fine geometric sizes of the occlusions in the crystal. The analysis shows that the effects of the primary design parameters on anisotropy can achieve 2-3 dB of axial difference for the biaxially diectric crystal. Although, only the dielectric case is presented, the multivariate estimation method used to estimate the material parameters is applicable for characterizing lossy and magnetic materials.